Preparation method of multi-curved-hole fiber base membrane of lithium battery separator

Through co-spinning and plasma surface treatment technology of polyvinylidene fluoride and closed polyurethane prepolymer, a multi-curved fiber base film was prepared, which solved the thermal safety problem of lithium battery separators under extreme conditions and improved the lithium battery's Ion conductivity and mechanical properties achieve higher electrochemical stability and thermal stability.

CN119315213AInactive Publication Date: 2025-01-14JIANGSU OLITER ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411437306.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lithium battery separators are prone to safety problems due to heat shrinkage or fuse under overcharge/overdischarge or extreme conditions, and the inorganic coating lacks lithium ion conduction capabilities, which cannot effectively solve the thermal safety and conductivity problems.

Method used

Polyvinylidene fluoride and closed polyurethane prepolymer are co-spinned to prepare multi-curved fiber base films, and the porosity, liquid absorption and mechanical properties are improved by film composite, hot pressing curing and plasma surface treatment. Enhance the conductivity of lithium ion.

Benefits of technology

It achieves high liquid absorption rate, strong ionic conductivity, good thermal stability and mechanical properties, and improves the safety and electrochemical performance of lithium battery separators.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a multi-curved-hole fiber base membrane of a lithium battery separator, which comprises the following steps: adding polyvinylidene fluoride and a closed polyurethane prepolymer in a mass ratio of 100: (5-20) into an electrostatic spinning solvent, and stirring and dissolving at 50-60 DEG C to obtain a co-spinning solution; the co-spinning solution is subjected to electrospinning through an electrostatic spinning machine, and a superfine fiber non-woven membrane is obtained; the superfine fiber non-woven film is subjected to adhesive film composite treatment for 15-20 min at the temperature of 120-150 DEG C, and then is subjected to hot-pressing curing treatment for 30-120 min at the temperature of 100-120 DEG C; and placing for 1-3 days under the conditions of room temperature and air humidity of 50-70% to complete the deblocking reaction of the closed polyurethane prepolymer, thereby obtaining the multi-curved-hole fiber base membrane for the lithium battery. The composite material has relatively high ionic conductivity, good thermal stability, chemical stability and electrochemical stability, and keeps high wettability and excellent mechanical properties to electrolyte in a repeated charging and discharging process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium ion battery materials, and in particular to a method for preparing a multi-curved hollow fiber-based membrane for a lithium battery separator. Background Art

[0002] Lithium-ion batteries have high energy density and cycle life, and are one of the preferred batteries for power devices and high-capacity electronic products. However, under extreme conditions of overcharge / overdischarge or other improper use, the temperature inside the lithium battery will rise rapidly, causing damage to the diaphragm, battery fire or explosion. Commonly used lithium battery diaphragms are mainly polyolefin polymer materials such as polypropylene (PP) and polyethylene (PE). These materials have high tensile strength and electrolyte wettability, but due to the need for pore formation during the preparation process, there is generally a stretching and pore expansion process. Even at higher temperatures that do not reach the glass transition temperature, there is a tendency to rebound, causing thermal shrinkage or diaphragm melting, leading to thermal safety problems; or a nano-inorganic oxide particle coating bonded by an inert polymer binder is coated on the surface of the diaphragm, but the inorganic particles in the existing inorganic coating slurry are mostly dense particles, which do not have lithium ion conductivity. Summary of the invention

[0003] Purpose of the invention: In order to solve the above technical problems, the present invention provides a method for preparing a multi-porous fiber-based membrane for a lithium battery separator, so as to solve the problem of effectively improving the porosity and liquid absorption rate of the separator while having good mechanical properties and thermal stability.

[0004] Technical content: To achieve the above invention purpose, the technical solution adopted by the present invention is as follows: A method for preparing a multi-porous fiber-based membrane for a lithium battery separator, comprising the following steps: S1, adding polyvinylidene fluoride and blocked polyurethane prepolymer in a mass ratio of 100:5-20 into an electrospinning solvent, stirring and dissolving at 50-60° C. to obtain a co-spinning solution with a mass fraction of 8-20%; S2, electrospinning the co-spinning solution through an electrospinning machine to obtain an ultrafine fiber non-woven membrane; S3, the ultrafine fiber nonwoven membrane obtained in step S2 is subjected to a film composite treatment at 120-150° C. for 15-20 min, and then subjected to a hot pressing curing treatment at 100-120° C. for 30-120 min; S4, at room temperature and air humidity of 50-70%, leaving the blocked polyurethane prepolymer for 1-3 days to complete the deblocking reaction, thereby obtaining the lithium battery multi-porous fiber-based membrane.

[0005] Furthermore, the preparation method of the blocked polyurethane prepolymer comprises the following steps: (1) dissolving caprolactam in toluene to obtain a toluene solution of caprolactam for later use; (2) Put the polyurethane prepolymer and toluene in a mass ratio of 2-3:1 into a three-necked reaction bottle, stir and mix them evenly, then add the toluene solution of caprolactam by dropwise addition while maintaining continuous stirring at a temperature of 60-70°C, the molar ratio of the polyurethane prepolymer to caprolactam is controlled in the range of 1:1-1.5, the reaction temperature is raised to 70-90°C and the reaction is carried out for 3-6 hours to obtain a closed polyurethane prepolymer.

[0006] Furthermore, it also includes a base membrane plasma surface treatment step: placing a lithium battery multi-porous fiber base membrane into a reaction chamber of a plasma treatment device, evacuating to a vacuum degree below 5Pa, using oxygen as a replacement gas, and generating plasma by radio frequency inductive coupling after replacement, and performing plasma excitation for 60-90s under conditions of 150W power and radio frequency frequency of 14MHz to obtain a lithium battery multi-porous fiber base membrane with plasma surface treatment.

[0007] Furthermore, the mass ratio of caprolactam to toluene in step (1) is 3:1.

[0008] Furthermore, the electrospinning solvent is a mixture of DMF and ACE, or a mixture of DMF and NMP.

[0009] Beneficial effects: Compared with the prior art, the lithium battery multi-porous fiber-based membrane of the present invention is a two-component nanofiber membrane obtained by co-spinning of a polyvinylidene fluoride / polyurethane blend system. The polyvinylidene fluoride and polyurethane in the membrane exist in the form of fibers at the same time, and have high liquid absorption rate, porosity and strong ion conductivity. After heat treatment, the polyurethane fibers are bonded together, the force per unit cross-sectional area is increased, and the tensile strength of the fiber membrane is increased. At the same time, through oxygen plasma discharge treatment, oxygen-containing functional groups can be introduced on the polymer surface, the wettability of the diaphragm is improved, and the CC on the polymer surface is interrupted, the short-chain molecules on its surface are ablated, and the amorphous and crystalline areas on the polymer surface are removed to a certain extent, and the adhesion between the lithium battery multi-porous fiber-based membrane and the inorganic nano-coating is improved. The present invention has high ionic conductivity, good thermal stability, chemical stability and electrochemical stability, and maintains high wettability and excellent mechanical properties to the electrolyte during repeated charging and discharging. DETAILED DESCRIPTION

[0010] The present invention will be further explained below in conjunction with specific examples, and it should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, the modifications of various equivalent forms of the present invention by those skilled in the art all fall within the scope defined by the appended claims of the present application. However, it is easy for those skilled in the art to understand that the specific material proportions, process conditions and results thereof described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims. Example

[0011] Put a polyurethane prepolymer and toluene in a mass ratio of 3:1 into a three-necked reaction bottle, mix them evenly, then dissolve caprolactam in toluene, wherein the molar ratio of the polyurethane prepolymer to caprolactam is 1:1, then add it dropwise into the reaction bottle with stirring, raise the reaction temperature to 70-90°C, and react at a constant temperature for 3-6 hours to obtain a closed polyurethane prepolymer; Polyvinylidene fluoride and blocked polyurethane prepolymer in a mass ratio of 100:5 are mixed and added into a mixed solvent of DMF (dimethylacetamide) / N-methylpyrrolidone in a mass ratio of 1:1, and dissolved by stirring at 50-60°C to obtain a co-spinning solution with a mass fraction of 8%; the co-spinning solution is loaded into an electrospinning device for electrospinning to obtain an ultrafine fiber non-woven membrane.

[0012] The electrospinning parameters are: spinning temperature 20°C, spinning relative humidity 30%, spinning voltage 10KV, receiving distance 10cm, solution flow rate 0.2ml / h, receiver speed 100-500rpm; the ultrafine fiber non-woven membrane is treated at 150°C for 15-20min, and then at 100°C for 30-120min, the closed polyurethane prepolymer is unsealed, and then placed at room temperature and air humidity of 50-70% for 1-3 days to obtain the lithium battery multi-porous fiber-based membrane.

[0013] The lithium battery porous fiber-based membrane is placed in the reaction chamber of a plasma treatment device, and after the vacuum degree is evacuated to 2Pa, oxygen is used as a replacement gas. After the replacement, plasma is generated by radio frequency inductive coupling. The plasma is excited for 60-90s under the conditions of 100W power and radio frequency frequency of 12MHz to obtain a lithium battery porous fiber-based membrane with plasma surface treatment.

[0014] Performance characterization: The tensile strength of the high-performance and stable lithium battery composite membrane prepared in this embodiment is 33.8 MPa, the elongation at break is 57.5%, the thermal shrinkage at 150°C is 1.5%, and the ionic conductivity is 6.5×10 -3 S·cm-1. Example

[0015] Put the polyurethane prepolymer and toluene in a mass ratio of 3:1 into a three-necked reaction bottle, mix them evenly, then dissolve caprolactam in toluene, wherein the molar ratio of the polyurethane prepolymer to caprolactam is 1:1.5, then add it dropwise into the reaction bottle with stirring, raise the reaction temperature to 70-90°C, and react at a constant temperature for 3-6 hours to obtain a closed polyurethane prepolymer; Polyvinylidene fluoride and blocked polyurethane prepolymer in a mass ratio of 100:20 are added to a mixed solvent of DMF / ACE (acetone) in a mass ratio of 7:3, and dissolved by stirring at 50-60°C to obtain a co-spinning solution with a mass fraction of 20%; the co-spinning solution is loaded into an electrospinning device for electrospinning to obtain an ultrafine fiber non-woven membrane.

[0016] The electrospinning parameters are as follows: spinning temperature 40°C, spinning relative humidity 60%, spinning voltage 30KV, receiving distance 20cm, solution flow rate 2ml / h, receiver speed 100-500rpm; the ultrafine fiber non-woven membrane is treated at 200°C for 15-20min, then at 120°C for 30-120min, the blocked polyurethane prepolymer is unsealed, and then placed at room temperature and air humidity of 50-70% for 1-3 days to obtain the lithium battery multi-porous fiber-based membrane.

[0017] The lithium battery porous fiber-based membrane is placed in the reaction chamber of a plasma treatment device, and after the vacuum degree is evacuated to 4Pa, oxygen is used as a replacement gas. After the replacement, plasma is generated by radio frequency inductive coupling. The plasma is excited for 60-90s under the conditions of 200W power and radio frequency frequency of 14MHz to obtain a lithium battery porous fiber-based membrane with plasma surface treatment.

[0018] Performance characterization: The tensile strength of the high-performance and stable lithium battery composite membrane prepared in this embodiment is 41.3 MPa, the elongation at break is 56.8%, the thermal shrinkage at 150°C is 0.5%, and the ionic conductivity is 7.1×10 -3 S cm -1 . Example

[0019] Put the polyurethane prepolymer and toluene in a mass ratio of 3:1 into a three-necked reaction bottle and mix them evenly. Then dissolve caprolactam in toluene, wherein the molar ratio of the polyurethane prepolymer to caprolactam is 1:1.1. Then, add it dropwise into the reaction bottle with stirring. The reaction temperature is raised to 70-90°C. The reaction is carried out at a constant temperature for 3-6 hours to obtain a closed polyurethane prepolymer.

[0020] Polyvinylidene fluoride and blocked polyurethane prepolymer in a mass ratio of 100:15 are added to a mixed solvent of DMF / N-methylpyrrolidone in a mass ratio of 1.5:1, and dissolved by stirring at 50-60°C to obtain a co-spinning solution with a mass fraction of 12%; the co-spinning solution is loaded into an electrospinning device for electrospinning to obtain an ultrafine fiber non-woven membrane.

[0021] The electrospinning parameters are as follows: spinning temperature 25°C, spinning relative humidity 50%, spinning voltage 15KV, receiving distance 12cm, solution flow rate 0.3ml / h, receiver speed 100-500rpm; the ultrafine fiber non-woven membrane is treated at 150°C for 15-20min, and then at 110°C for 30-120min, the blocked polyurethane prepolymer is unsealed, and then placed at room temperature and air humidity of 50-70% for 1-3 days to obtain the lithium battery multi-porous fiber-based membrane.

[0022] The lithium battery porous fiber-based membrane is placed in the reaction chamber of the plasma treatment device, and after the vacuum degree is evacuated to 3Pa, oxygen is used as the replacement gas. After the replacement, plasma is generated by radio frequency inductive coupling. The plasma is excited for 60-90s under the conditions of 150W power and radio frequency frequency of 14MHz to obtain a lithium battery porous fiber-based membrane with plasma surface treatment.

[0023] Performance characterization: The tensile strength of the high-performance and stable lithium battery composite membrane prepared in this embodiment is 44.7 MPa, the elongation at break is 58.2%, the thermal shrinkage at 150°C is 0.1%, and the ionic conductivity is 7.8×10 -3 S cm -1 .

[0024] The lithium battery multi-porous fiber-based membrane of the present invention is a two-component nanofiber membrane obtained by co-spinning of a polyvinylidene fluoride / polyurethane blend system. The polyvinylidene fluoride and polyurethane in the membrane exist in the form of fibers at the same time, and have high liquid absorption rate, porosity and strong ionic conductivity. After heat treatment, the polyurethane fibers are adhered to each other, the force per unit cross-sectional area is increased, and the tensile strength of the fiber membrane is increased. At the same time, through oxygen plasma discharge treatment, oxygen-containing functional groups can be introduced on the polymer surface, the wettability of the diaphragm is improved, and the CC on the polymer surface is interrupted, the short-chain molecules on its surface are ablated, and the amorphous and crystalline areas on the polymer surface are removed to a certain extent, and the adhesion between the lithium battery multi-porous fiber-based membrane and the inorganic nano-coating is improved. The present invention has high ionic conductivity, good thermal stability, chemical stability and electrochemical stability, and maintains high wettability and excellent mechanical properties to the electrolyte during repeated charging and discharging.

[0025] Finally, it should be noted that the above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A method for preparing a multi-porous fiber-based membrane for a lithium battery separator, characterized in that The following steps are involved: S1, adding polyvinylidene fluoride and blocked polyurethane prepolymer in a mass ratio of 100:5-20 into an electrospinning solvent, stirring and dissolving at 50-60° C. to obtain a co-spinning solution with a mass fraction of 8-20%; S2, electrospinning the co-spinning solution through an electrospinning machine to obtain an ultrafine fiber non-woven membrane; S3, the ultrafine fiber nonwoven membrane obtained in step S2 is subjected to a film composite treatment at 120-150° C. for 15-20 min, and then subjected to a hot pressing curing treatment at 100-120° C. for 30-120 min; S4, at room temperature and air humidity of 50-70%, leaving the blocked polyurethane prepolymer for 1-3 days to complete the deblocking reaction, thereby obtaining the lithium battery multi-porous fiber-based membrane.

2. The method for preparing the multi-porous fiber-based membrane for lithium battery separator according to claim 1, characterized in that: The preparation method of the blocked polyurethane prepolymer comprises the following steps: (1) dissolving caprolactam in toluene to obtain a toluene solution of caprolactam for later use; (2) Put the polyurethane prepolymer and toluene in a mass ratio of 2-3:1 into a three-necked reaction bottle, stir and mix them evenly, then add the toluene solution of caprolactam by dropwise addition while maintaining continuous stirring at a temperature of 60-70°C, the molar ratio of the polyurethane prepolymer to caprolactam is controlled in the range of 1:1-1.5, the reaction temperature is raised to 70-90°C and the reaction is carried out for 3-6 hours to obtain a closed polyurethane prepolymer.

3. The method for preparing the multi-porous fiber-based membrane for lithium battery separator according to claim 2, characterized in that: The method also includes a plasma surface treatment step of the base membrane: placing the lithium battery porous fiber base membrane into a reaction chamber of a plasma treatment device, evacuating the chamber to a vacuum degree below 5 Pa, using oxygen as a replacement gas, and generating plasma by radio frequency inductive coupling after the replacement, and performing plasma excitation for 60-90 seconds under conditions of a power of 150 W and a radio frequency frequency of 14 MHz to obtain a plasma surface treated lithium battery porous fiber base membrane.

4. The method for preparing the multi-porous fiber-based membrane for lithium battery separator according to claim 1, characterized in that: The mass ratio of caprolactam to toluene in step (1) is 3:

1.

5. The method for preparing the multi-porous fiber-based membrane for lithium battery separator according to claim 1, characterized in that: The electrospinning solvent is a mixture of DMF and ACE, or a mixture of DMF and NMP.

Citation Information

Patent Citations

  • Enhanced bi-component nanofiber porous membrane and preparation method thereof

    CN102140734A

  • Hypervolume stable lithium battery and preparation method thereof

    CN109346655A